Construction and Antiapoptosis Activities of Recombinant Adenoviral Expression Vector Carrying EBV Latent Membrane Protein 2A - Xishuang Liu; Yu Gao; Bing Luo; Youan Zhao (Gastroenterology Research and Practice)
To evaluate the possible effects of LMP2A (EBV latent membrane protein 2A) on human gastric cancer cell line SGC-7901, LMP2A coding gene was subcloned into shuttle plasmid pAdTrackCMV to form transfer plasmid pAdTrackCMV-2A, which was linearized with PmeI and cotransformed into E.coli BJ5183 with adenovirus genomic plasmid of pAdeasy-1. The identified recombinant adenovirus plasmid DNA was digested with PacI and transfected into 293 cells to package recombinant adenovirus particles named vAd-2A. Then the expression and antiapoptosis activities of LMP2A on SGC-7901 infected with vAd-2A were analyzed. The vAd-2A was successfully constructed and identified by PCR, restriction digestion, and sequencing. LMP2A expression in SGC was identified by strong green fluorescence expression with fluorescence microscopic photograph and Southern blotting. The growth of LMP2A expressing SGC cells was apparently improved. Both cyclin E expression and S phase ratio in LMP2A expressing SGC cells were upregulated by cell cycle analysis and confocal microscopic analysis respectively. The replication-deficient recombinant adenovirus vector can express LMP2A antigen in SGC cells and inhibit their apoptosis. The results indicate that LMP2A might play an important role in pathogenesis of EBV-associated gastric cancer (EBVaGC). This study establishes a foundation for further study on EBVaGC and its gene therapy.